A preliminary evaluation of targeted nanopore sequencing technology for the detection of Mycobacterium tuberculosis in bronchoalveolar lavage fluid specimens - Sun, Xiaoke; Song, Jingchao; Leng, Xia; Li, Fuli; Wang, Haojie; He, Jiaqian; Zhai, Wenhua; Wang, Zhenjing; Wu, Qingqing; Li, Zheng; Ruan, Xianglin (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To evaluate the efficacy of targeted nanopore sequencing technology for the detection of Mycobacterium tuberculosis(M.tb.) in bronchoalveolar lavage fluid(BALF) specimens. Methods A prospective study was used to select 58 patients with suspected pulmonary tuberculosis(PTB) at Henan Chest Hospital from January to October 2022 for bronchoscopy, and BALF specimens were subjected to acid-fast bacilli(AFB) smear, Mycobacterium tuberculosis MGIT960 liquid culture, Gene Xpert MTB/RIF (Xpert MTB/RIF) and targeted nanopore sequencing (TNS) for the detection of M.tb., comparing the differences in the positive rates of the four methods for the detection of patients with different classifications. Results Among 58 patients with suspected pulmonary tuberculosis, there were 48 patients with a final diagnosis of pulmonary tuberculosis. Using the clinical composite diagnosis as the reference gold standard, the sensitivity of AFB smear were 27.1% (95% CI: 15.3-41.8); for M.tb culture were 39.6% (95% CI: 25.8-54.7); for Xpert MTB/RIF were 56.2% (95% CI: 41.2-70.5); for TNS were 89.6% (95% CI: 77.3-96.5). Using BALF specimens Xpert MTB/RIF and/or M.tb. culture as the reference standard, TNS showed 100% (30/30) sensitivity. The sensitivity of NGS for pulmonary tuberculosis diagnosis was significantly higher than Xpert MTB/RIF, M.tb. culture, and AFB smear. Besides, P values of <0.05 were considered statistically significant. Conclusion Using a clinical composite reference standard as a reference gold standard, TNS has the highest sensitivity and consistency with clinical diagnosis, and can rapidly and efficiently detect PTB in BALF specimens, which can aid to improve the early diagnosis of suspected tuberculosis patients.